PENGARUH DISIPLIN DAN MOTIVASI KERJA TERHADAP KINERJA GURU DI SMP N 3 BELITANG MADANG RAYA KABUPATEN OKU TIMUR - Erlysa Ivana A. (STIE DWI SAKTI BATURAJA, 2017)
This research analyse influence of discipline and motivation work to performance learn in public school SMP 3 Great Belitang Madang of Sub-Province of OKU East. This research aim to know by empirik about influence between discipline work to performance learn in public school SMP 3 Great Belitang Madang of Sub-Province of OKU East, influence between motivation work with performance learn in public school SMP 3 Great Belitang Madang of Sub-Province of OKU East, influence between discipline work and motivation work to performance learn in public school SMP 3 Great Belitang Madang of Sub-Province of OKU East. This research is conducted by using method analyse correlation, analyse regresi, statistical test. Result of this research can be told as follows ( 1) Pursuant to obtained score and result of research show variable owning biggest mean score motivation. ( 2) Discipline have an effect on signifikan to teacher performance. ( 3) Motivation have an effect on signifikan to teacher performance. ( 4) Discipline and motivation work by together have an effect on signifikan to teacher